Agricultural Pesticide Use in Florida: A Summary, 2007-2009 - Bonnie Wells; Frederick M. Fishel (EDIS)
Commercial farms in Florida span over nine million acres and earn annual profits of more than $7.5 billion. High temperatures and heavy rainfall create heavy pest pressure that leads the majority of Florida farmers to rely up on pesticides for high-yielding, cost-effective crop production. This 4-page fact sheet lists top ten pesticides and the crops associated with this use, and also specifies the most common fungicides, insecticides, herbicides, and other pesticides. Written by Bonnie Wells and F.M. Fishel, and published by the UF Department of Agronomy, June 2011.